Warning of impacts of climate change on coastal islands - a case study for Co To island - An, Le Duc; Khanh, Uong Dinh; Dung, Bui Quang; Huong, Nguyen Thi (Vietnam Journal of Earth Sciences, 2014)
This study includes following steps:- Using “Scenarios of Climate Change, Sea level rise for Vietnam” established by the Ministry of Natural Resources and Environment (2011) to calculate temperature, rainfall, and sea level rise in Co To island by the end of this Century under the high emission scenario.- Impact assessment of the elements (temperature, rainfall, and sea level rise) on meteoro-hydrologycal processes (rainfall, inundation) as well as geomorphological ones (landslide, rockfall, coast erosion, soil erosion, salt-water intrusion, and change in coastal landforms). The assessment of the inundated area is based not only on the distance of sea level rise but also on the coast retreat due to erosion, and the maximum tidal range.- Assessment of the impacts on the local production and life.The impact assessment result shows that CoTo island will lose about 200 ha due to inundation and 215 ha because of tidal influence, which are not very large areas (25% of island surface), but the most valuable lands, including populated areas, beaches, rice-fields, with important buildings (roads, dikes, dams, reservoirs, etc). Moreover, unfavourable exogenic processes will also increase in term of frequency and intensity violently, such as coastal erosion, landslide in hill and low mountains, escarp rockfall, land degradation in upland areas, saltwater intrusion in unconsolidated aquifer, and wave and storm are likely to be more intensified; it is predicted also that Co To island is separated into two parts. Consequently, the life of local people in the island will become less stable because of its more severe environment and their livelihood will have to face more challenges. Adaptable solutions, therefore, should begiven as soon as possible.